2022
DOI: 10.3390/cancers14194813
|View full text |Cite
|
Sign up to set email alerts
|

The Lung Microbiota and Lung Cancer: A Growing Relationship

Abstract: The lung is home to a dynamic microbial population crucial to modulating immune balance. Interest in the role of the lung microbiota in disease pathogenesis and treatment has exponentially increased. In lung cancer, early studies suggested an important role of dysbiosis in tumor initiation and progression. These results have helped accelerate research into the lung microbiota as a potential diagnostic marker and therapeutic target. Microbiota signatures could represent diagnostic biomarkers of early-stage dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 104 publications
0
4
0
Order By: Relevance
“…32 The lung microbiome, in particular, has shown promise as a diagnostic marker and a therapeutic target for lung cancer, especially in the early stages of Food & Function Paper cancers. 33,34 Gut microbiome characteristics have also been explored as potential markers for predicting early lung cancer. 35 In summary, disturbances in the gut microbiome can promote lung cancer progression through various mechanisms, making the gut microbiome a potential diagnostic marker and therapeutic target for lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…32 The lung microbiome, in particular, has shown promise as a diagnostic marker and a therapeutic target for lung cancer, especially in the early stages of Food & Function Paper cancers. 33,34 Gut microbiome characteristics have also been explored as potential markers for predicting early lung cancer. 35 In summary, disturbances in the gut microbiome can promote lung cancer progression through various mechanisms, making the gut microbiome a potential diagnostic marker and therapeutic target for lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…While balanced bacterial interactions are necessary for immune system drug interactions 7 , some microbial interactions may also undermine chemotherapy treatment and thus contribute to chemotherapy resistance or failure. Examples include metabolising drugs before they can be effective, as seen in Mycoplasma with gemcitabine 5,9,16 ; acting as carcinogens as with Fusobacterium nucleatum and oxaliplatin 18,20,25,26 ; and producing toxins with side effects so severe that they are intolerable for the patient such as with β-glucuronase with irinotecan 27,28,30,31 . Effects vary even between strains of the same species of bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Higher rates of bacterial infections in cancerous tumours 7,9,16 suggest either a causal relationship as a carcinogen 20,21 , an increased attraction of bacteria to the tumour micro-environment 6,11,16,18 , or both; there is no consensus as of yet 5 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the involvement of the gut microbiome in treatment response has been well documented in the development and immunotherapy of lung cancer [30,31], recent studies suggest that the microbiota in the lungs also play a role in lung cancer development [32][33][34][35]. Microorganisms such as bacteria, viruses, and fungi have emerged as pivotal players in the complex interplay of factors contributing to cancer initiation, promotion, and progression [36] and lung cancer development [32,33]. Studies have reported that the levels of Actinomyces, Veillonella, Streptococcus, Megasphaera, and Mycobacterium were more abundant in patients with lung cancer compared with healthy individuals [37][38][39].…”
Section: Introductionmentioning
confidence: 99%